2015
DOI: 10.5937/geopan1501020s
|View full text |Cite
|
Sign up to set email alerts
|

Research on the surface water quality in mining influenced area in north-western part of Romania

Abstract: The paper highlights the current situation of the quality of surface water in the areas influenced by mining activities in the north-western part of Romania. In this respect a series of investigations have been conducted regarding the contamination with heavy metals of the water of the Someş and Tisa hydrographic Basins, which cover the northern part of Maramures County and the south-western area of Maramures County, respectively.The results of the comparative research refer to the period between 1999 and 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
1
6
5
Order By: Relevance
“…From Table 2, there was a high mean concentration of Pb across locations except in GS where concentration is moderate but the mean concentrations of all sampling locations including GS were above the (WHO 2011) guideline standard of 0.01mg/l for water quality. The presence of traces of Pb in surface water constitute a growing concern [10] because human exposure to high Pb levels have considerable cumulative effects that would result in fatal health consequences [4]. The average concentration values were high for Pb obtained in this study but are lower than the peak values obtained in another study in Nigeria [25].…”
Section: (Mg/lcontrasting
confidence: 54%
See 1 more Smart Citation
“…From Table 2, there was a high mean concentration of Pb across locations except in GS where concentration is moderate but the mean concentrations of all sampling locations including GS were above the (WHO 2011) guideline standard of 0.01mg/l for water quality. The presence of traces of Pb in surface water constitute a growing concern [10] because human exposure to high Pb levels have considerable cumulative effects that would result in fatal health consequences [4]. The average concentration values were high for Pb obtained in this study but are lower than the peak values obtained in another study in Nigeria [25].…”
Section: (Mg/lcontrasting
confidence: 54%
“…There is a wide array of studies on surface water quality in mining environments worldwide [8][9][10][11][12][13]. Also, in Africa several studies on surface water in mining areas were reported [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The surface water samples had small amounts of Fe (0.07 mgL −1 ) in sample P2 and Mn (3.903 mgL −1 ) in sampling point P3, being below the limit values. The amount of Fe (0.07 mgL −1 ) in the water samples taken in 2022 is much lower compared to the samples analyzed by Smical et al (0.55 mgL −1 ) in 2011 [16]. Instead, the amount of Mn (3.903 mgL −1 ) is almost four times higher than the value obtained by Smical et al, (1.18 mgL -1 ) [16].…”
Section: General Characteristics Of the Surface Watercontrasting
confidence: 50%
“…The amount of Fe (0.07 mgL −1 ) in the water samples taken in 2022 is much lower compared to the samples analyzed by Smical et al (0.55 mgL −1 ) in 2011 [16]. Instead, the amount of Mn (3.903 mgL −1 ) is almost four times higher than the value obtained by Smical et al, (1.18 mgL -1 ) [16].…”
Section: General Characteristics Of the Surface Watercontrasting
confidence: 50%
See 1 more Smart Citation